Faking or Convincing: Why Do Some Advertising Campaigns Win Creativity Awards? - Raoul V. Kübler; Dennis Proppe (BuR - Business Research, 2012)
Since the Sarbanes-Oxley Act was passed in 2002, it has become commonplace in the advertising industry to use creativity-award-show prizes instead of gross income figures to attract new customers. Therefore, achieving a top creativity ranking and winning creativity awards have become high priorities in the advertising industry. Agencies and marketers have always wondered what elements in the advertising creation process would lead to the winning of creativity awards. Although this debate has been dominated by pure speculation about the success of different routines, approaches and strategies in winning creativity awards, for the first time our study delivers an empirical insight into the key drivers of creativity award success. We investigate what strategies and which elements of an advertising campaign are truly likely to lead to winning the maximum number of creativity awards. Using a sample of 108 campaigns, we identify factors that influence campaign success at international advertising award shows. We identify innovativeness and the integration of multiple channels as the key drivers of creativity award success. In contrast to industry beliefs, meaningful or personally connecting approaches do not seem to generate a significant benefit in terms of winning creativity awards. Finally, our data suggest that the use of so-called fake campaigns to win more creativity awards does not prove to be effective.
urn:nbn:de:0009-20-33124
Keywords: 650; advertising agencies; advertising award shows; creative success; fake campaigns; new business; partial least squares; Werbewirtschaft; Kreativität; Preisverleihung; Marketingmanagement; Deutschland